Integrating Power-to-Methane with Carbon Capture (P2M-CC) for Sustainable Decarbonization in Cement Manufacturing - Cristian Dincă; Nela Slavu (Energies)
The cement industry is one of the industries with the highest contribution to global CO2 emissions due to its energy-intensive processes and the use of fossil fuels. This study evaluates the integration of the P2M-CC (power-to-methane with carbon capture) concept in cement plants to reduce the carbon footprint of the cement produced. Three cement plant modernization scenarios, involving replacing natural gas with synthetic methane obtained by methanation of green hydrogen and CO2 captured from the industrial process, were analyzed. The results show that integrating the P2M-CC concept reduced the CO2 emission factor from 789 kg/ton cement (baseline scenario) to 85 kg/ton (in all analyzed scenarios). However, the initial investment costs increased significantly by 5.8 times in S2.2, 5.2 times in S2.3, and 13 times in S2.1, compared to the baseline scenario, by adding the necessary equipment for electrolysis, methanation, and CO2 capture. On the other hand, operating costs decreased the most in S2.2, by 42.2% compared to the baseline scenario, while in S2.1, they decreased by 10.9%, and in S2.3, they increased by 141%. The ideal scenario (S2.2) showed the best economic and environmental performance, with an LCOC of 71 €/ton of cement and an NPV of 2609 million €, due to excess electricity produced by the wind plants without additional investment costs. In contrast, the complete scenario (S2.1), characterized by significant investments in wind power plants and CO2 capture technology, showed an LCOC of 297 €/ton of cement, while the realistic scenario (S2.3), with high operational costs, had an LCOC of 333 €/ton cement. Using synthetic methane in all proposed scenarios reduced fossil fuel dependency and CO2 emissions.